AB0031 Anti-inflammatory property of hdl in nod1 ligand induced kawasaki arteritis in mice. (23rd January 2014) - Kono, H.; Yanagida, T.; Kikuchi, H.; Asako, K.; Takayama, M.
Abstract : Background: Atherosclerosis is a chronic metabolic disease of inflammatory processes. Immune cells including monocytes are recruited to the subintimal lesion of the vascular wall and store lipids to transform themselves to the foam cells. The lipid profiles in the serum are shown to be risk factors for developing atherosclerosis, such as high LDL (low density lipoprotein) or low HDL (high density lipoprotein) concentration. In addition to deliver cholesterol from vascular wall to liver, HDL is supposed to exert antiinflammatory properties which are not well characterized. We recently indentified that HDL exert an antiinflammatory property which is not ascribed to it's capacity to lower the cholesterol level of the peripheral tissue. Objectives: To investigate the antiinflammatory function of reconstituted HDL (rHDL) in the Kawasaki arteritis murine model in vivo. Methods: Coronary arteritis mimicking Kawasaki disease was induced by administrating 20 microgram of lipopolysaccharide followed by weekly injection of 500 microgram of the nucleotide-binding oligomerization domain 1 (NOD1) ligand FK-565 for 4 times. 2 mg of rHDL or control PBS was injected 4 times along with FK-565 administration. After a week after the last injection of FK-565 or control PBS, the severity of coronary arteritis was quantified by measuring the inflammation area surrounding the coronary arteries on the microscopic images. The cytokine levels of the serum were determined by multiplex. Results: The rHDL treatment reduced the inflammatory area of coronary arteries compared with the control PBS treated groups, showing statistically significance (P=0.008 with Student t-test, 0.29±0.24 mm 2 (PBS control group) and 0.13±0.07 mm 2 (rHDL group)). Serum level of IL-12p40 was decreased in mice treated with rHDL. Conclusions: The data indicate that rHDL exert an antiinflammatory activity in the NOD1 ligand induced Kawasaki arteritis model in vivo. References: Nishio H et al. Arterioscler Thromb Vasc Biol . 2011, 31: 1093-9 Disclosure of Interest: None Declared